2022
DOI: 10.1021/acs.energyfuels.2c03070
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Diffusion in Organic-Rich Porous Media: Implications for Hydrogen Geo-storage

Abstract: Subsurface hydrogen storage for large-scale energy supply to decarbonize a variety of greenhouse gas-emitting activities is gaining momentum worldwide to combat climate change. Hydrogen’s extensive range of flammable concentrations and low minimum ignition energy in air combined with its highly diffusive nature mandate implementation of comprehensive risk management protocols to maintain storage safety. In particular, the role of hydrogen diffusion process (self-diffusion) needs further investigation to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…They also reported that hydrogen adsorption in coals is 5 times less compared to that of CO 2 adsorption at various temperature conditions. Raza et al 73 integrated molecular dynamics simulation to study hydrogen self-diffusivity in shales. They observed that increasing the pressure resulted in reducing the diffusivity, regardless of the pore size or kerogen type.…”
Section: Hydrogen Diffusivity and Adsorptionmentioning
confidence: 99%
“…They also reported that hydrogen adsorption in coals is 5 times less compared to that of CO 2 adsorption at various temperature conditions. Raza et al 73 integrated molecular dynamics simulation to study hydrogen self-diffusivity in shales. They observed that increasing the pressure resulted in reducing the diffusivity, regardless of the pore size or kerogen type.…”
Section: Hydrogen Diffusivity and Adsorptionmentioning
confidence: 99%
“…118 However, the content of Ca 2+ or Mg 2+ varies greatly among them. 119 In the process of geological sequestration, it is crucial to select a suitable site during the process of geological sequestration. 100 Therefore, selecting silicate strata rich in calcium and magnesium ions or sandstone strata with more and smaller silicate mineral particles, would be more conducive to CO 2 mineralization.…”
Section: The Effect Of Mineralmentioning
confidence: 99%
“…For instance, the adsorption isotherms of hydrogen, methane, ethylene, and their binary and ternary mixtures were studied [88]. The diffusion rates of hydrogen, methane, and carbon dioxide in organic kerogen nanopores were investigated [89]. The adsorption of pure H 2 , H 2 mixed with CH 4 , and H 2 mixed with CO 2 in representative kerogen and MMT were studied using grand canonical Monte Carlo (GCMC) [90].…”
Section: Adsorption Of Hydrogen In Shalementioning
confidence: 99%
“…Comparison of the adsorption of hydrogen and methane in shale showed that the adsorption of both gases increased with increasing pressure [88][89][90][91][92][93]. The adsorption rate gradually decreased with increasing pressure, and the adsorption behavior of methane and hydrogen was Type I Kerogen (organic matter rich in algae and fungal remnants) [88][89][90].…”
Section: Adsorption Of Hydrogen In Shalementioning
confidence: 99%